Educational System of John Dewey - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 1996)
John Dewey was one of the most prominent representatives of pedagogy of action, who supported the idea of a new, “active” school. The article presents a short life history of J. Dewey, describes the scope of his scientific interests. The description of characteristics of pupils of different age groups is presented, outlooks of Dewey towards development of character traits of children are described. The article argues that Dewey was a representative of pedocentristic orientation in education: he based his educational theory solely on children’s interests and their personal experience. The task of school, according to Dewey, is to foster the natural development of children. Dewey was also interested in problems of sociology of education. He considers school first of all as a social organism. Dewey developed a theory of intellectual development, which is still important at present time.